Insulambacter thermoxylanivorax sp. nov., a thermophilic xylanolytic bacterium isolated from compost - Chhe, Chinda; Uke, Ayaka; Baramee, Sirilak; Tachaapaikoon, Chakrit; Pason, Patthra; Waeonukul, Rattiya; Ratanakhanokchai, Khanok; Kosugi, Akihiko (International Journal of Systematic and Evolutionary Microbiology, 2023)
We isolated and analysed a Gram-negative, facultatively thermophilic, xylan-degrading bacterium that we designated as strain DA-C8 T . The strain was isolated from compost from Ishigaki Island, Japan, by enrichment culturing using beech wood xylan as the sole carbon source. The strain showed high xylan degradation ability under anaerobic growth conditions. The isolate grew at 37–60 °C (optimum, 55 °C) and pH 4.0–11.0 (optimum, pH 9.0). As well as xylan, strain DA-C8 T could use polysaccharides such as arabinoxylan and galactan as carbon sources. Comparison of 16S rRNA gene sequences indicated that strain DA-C8 T was most closely related to Paenibacillus cisolokensis LC2-13A T (93.9 %) and Paenibacillus chitinolyticus HSCC596 (93.5 %). In phylogenetic analysis, strain DA-C8 T belonged to the same lineage as Xylanibacillus composti K13 T (92.5 %), but there was less statistical support for branching (70 %). Digital DNA–DNA hybridization, average nucleotide identity values and average amino acid sequence identity between strain DA-C8 T and P. cisolokensis LC2-13A T were 21.8, 68.3 and 58.2 %, respectively. Those between strain DA-C8 T and X. composti K13 were 23.7, 67.7 and 57.6 %, respectively. The whole-genome DNA G+C content of strain DA-C8 T was 52.3 mol%. The major cellular fatty acids were C 16 : 0 (42.9 %), anteiso-C 15 : 0 (20.0 %) and anteiso-C 17 : 0 (16.7 %), the major quinone was menaquinone 7, and the major polar lipids were unidentified glycolipids. On the basis of phenotypic, chemotaxonomic and phylogenetic evidence, a novel genus is proposed— Insulambacter gen. nov.—for the novel species Insulambacter thermoxylanivorax sp. nov. The type strain is DA-C8 T (=JCM 34211 T =DSM 111723 T ).